Richard Granville Bromley (1939-2018) – Understanding the chalk. Issue 6 (December 2020) - Gale, Andy
Abstract: Richard Bromley was an exceptional geologist, naturalist and trace fossil expert who revolutionised our understanding of the interactions of animals and sediments, and described and illustrated in exquisite detail the fabrics formed in the process. He also made major contributions to the study of chalk, particularly the formation and modification of hardgrounds and the fabrics produced by burrowing and boring organisms in the sediment; the review presented here focuses on this part of his contribution.